2019
DOI: 10.3390/coatings9020073
|View full text |Cite
|
Sign up to set email alerts
|

Towards Functional Silicon Nitride Coatings for Joint Replacements

Abstract: Silicon nitride (SiNx) coatings are currently under investigation as bearing surfaces for joint implants, due to their low wear rate and the good biocompatibility of both coatings and their potential wear debris. The aim of this study was to move further towards functional SiNx coatings by evaluating coatings deposited onto CoCrMo surfaces with a CrN interlayer, using different bias voltages and substrate rotations. Reactive direct current magnetron sputtering was used to coat CoCrMo discs with a CrN interlaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…It was shown that those types of SiNx coatings have a higher coefficient of friction (163%) compared to uncoated samples during run-in phase, 47 notwithstanding Figure 7. Microscopic view onto the proximal coated male taper surface (Ti stem) after disassembly using laser microscopy.…”
Section: Discussionmentioning
confidence: 90%
“…It was shown that those types of SiNx coatings have a higher coefficient of friction (163%) compared to uncoated samples during run-in phase, 47 notwithstanding Figure 7. Microscopic view onto the proximal coated male taper surface (Ti stem) after disassembly using laser microscopy.…”
Section: Discussionmentioning
confidence: 90%
“…A previous study by Filho et al [38] evaluated the wear resistance of SiN x coatings deposited with 1- and 3-fold rotation (needed for future implant deposition) in a ball-on-disc system, in a hard-on-hard contact. While all coatings showed low wear rates against the Si 3 N 4 balls, it was found that the three-fold rotation reduced the coating density, which could influence the performance of the coating in its targeted application.…”
Section: Introductionmentioning
confidence: 99%
“…TiN coatings are also used extensively in the field of biomedicine, thanks to their resistance to wear and high biocompatibility. Therefore, TiN coatings are currently available on the market for knee replacements, particularly aimed at hypersensitive patients [ 40 ]. Chiang et al [ 41 ] reported on the relationship between the water contact angle on TFMG-coated surfaces and the presence of bacteria.…”
Section: Resultsmentioning
confidence: 99%